2016
DOI: 10.1111/anae.13622
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of single‐use bronchoscopes in critically ill patients

Abstract: SummaryDisposable bronchoscopes such as the Ambu aScope TM 3 are marketed as 'single use' The risks of contamination from prolonged device storage before possible re-use are unknown. Following clinical bronchoscopy in patients whose lungs were mechanically ventilated, 20 aScope TM 3's bronchoscopes received a standard 'social clean' and were then stored. Subsequent paired saline flush and swab samples were taken at time zero, and at 24 h and 48 h. Positive microbiological cultures were obtained from at least o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…However, even less is known about the practice of re-using singleuse devices in the same patient. In this edition of Anaesthesia, McGrath and colleagues have published their very practical test of potential harm from 'same patient' re-use of the Ambu aScope3 TM (Ambu Ltd, St Ives, Cambridgeshire, UK) single-use bronchoscope device [3]. They demonstrated a consistent ability of pathogenic bacteria to withstand standard bedside cleaning, and clearly showed that re-interpreting 'singleuse' devices, as 'single-patient' devices is dangerous, particularly when the time between procedures on that single patient is extended.…”
Section: Editorialmentioning
confidence: 99%
See 4 more Smart Citations
“…However, even less is known about the practice of re-using singleuse devices in the same patient. In this edition of Anaesthesia, McGrath and colleagues have published their very practical test of potential harm from 'same patient' re-use of the Ambu aScope3 TM (Ambu Ltd, St Ives, Cambridgeshire, UK) single-use bronchoscope device [3]. They demonstrated a consistent ability of pathogenic bacteria to withstand standard bedside cleaning, and clearly showed that re-interpreting 'singleuse' devices, as 'single-patient' devices is dangerous, particularly when the time between procedures on that single patient is extended.…”
Section: Editorialmentioning
confidence: 99%
“…We also note that many scientific journals favour systematic reviews because they tend to contribute to higher journal impact factors. However, the rise of systematic reviews should give cause for concern; more than 8000 are being indexed in MEDLINE annually, reflecting a three-fold increase over the last decade [3]. We write 'concern', because many of these reviews across healthcare seem to fall short of essential requirements such as incorporating risk of bias assessment in meta-analyses (only 16%), searching for unpublished data (only 7%), or not fully following a protocol (only one-third [3]).…”
Section: Editorialmentioning
confidence: 99%
See 3 more Smart Citations